Superparamagnetic and ferromagnetic behavior of ZnFe2O4 nanoparticles synthesized by microwave-assisted hydrothermal method - Phuruangrat A. (2017)
© 2017, Pleiades Publishing, Ltd. Zinc ferrite (ZnFe 2 O 4 ) nanoparticles were successfully synthesized from Zn(NO 3 ) 2 · 6H 2 O and Fe(NO 3 ) 3 · 9H 2 O by microwave hydrothermal method at 150°C for 1 h. Cubic ZnFe 2 O 4 with particle size below 7 nm was formed in the solution at pH ≥ 6. The crystallinity and particle size of ZnFe 2 O 4 nanoparticles were increased after calcination. The effects of pH of the precursor solution and calcination on the particle size and crystallinity of the particles were studied. At room temperature the products show superparamagnetic and ferromagnetic properties, determined by their size. The formation mechanism of ZnFe 2 O 4 was also discussed according to the experimental results.